Tales from the Trobriand Islands of Papua New Guinea : psycholinguistic and anthropological linguistic analyses of tales told by Trobriand children and adults - Senft, Gunter, 1952- (Culture and language use ;, 2015)
This volume presents 22 tales from the Trobriand Islands told by children (boys between the age of 5 and 9 years) and adults. The monograph is motivated not only by the anthropological linguistic aim to present a broad and quite unique collection of tales with the thematic approach to illustrate which topics and themes constitute the content of the stories, but also by the psycholinguistic and textlinguistic questions of how children acquire linearization and other narrative strategies, how they develop them and how they use them to structure these texts in an adult-like way. The tales are presented in morpheme-interlinear transcriptions with first textlinguistic analyses and cultural background information necessary to fully understand them. A summarizing comparative analysis of the texts from a psycholinguistic, anthropological linguistic and philological point of view discusses the underlying schemata of the stories, the means narrators use to structure them, their structural complexity and their cultural specificity.